Using Sustainable Landscape Design Criteria in Order to Regeneration of Urban Seasonal Rivers’ Bed - Reza Sadeghi, Ali; Ahmadi, Ferial (European Journal of Sustainable Development, 2017)
The present research has been conducted in order to preserve the Shiraz Khoshk River landscape as a dynamic ecosystem; moreover, to regenerate the quality of the riverbed through the implementation of landscape design criteria. Process recommendations to regenerate of the Khoshk River through landscape design are based on descriptive analysis of library research and case study, as well as observation and interview procedures with survey studies.Recommendations have been based on the study and analysis of multiple primary factors, including environmental, cultural, physical, and social features. Subsequent suggestions for designing a sustainable landscape have been provided, and have been focused on repair and protection of the landscape, and ecological and aesthetic principles. Emphasis has been placed on protection and improvement of the natural landscape and the diverse bionetwork of the region, the removal of inappropriate applications and bio- environmental pollutants, and the design of a suitable habitat for migratory birds. Keywords: Urban Seasonal River, Sustainable Landscape Design Criteria, Landscape conservation,Shiraz Khoshk River